Review of Pre-Ignition Research in Methanol Engines - Zhijie Li; Changhui Zhai; Xiaoxiao Zeng; Kui Shi; Xinbo Wu; Tianwei Ma; Yunliang Qi (Energies)
Methanol can be synthesized using green electricity and carbon dioxide, making it a green, carbon-neutral fuel with significant potential for widespread application in engines. However, due to its low ignition energy and high laminar flame speed, methanol is susceptible to hotspot-induced pre-ignition and even knocking under high-temperature, high-load engine conditions, posing challenges to engine performance and reliability. This paper systematically reviews the manifestations and mechanisms of pre-ignition and knocking in methanol engines. Pre-ignition can be sustained or sporadic. Sustained pre-ignition is caused by overheating of structural components, while sporadic pre-ignition is often linked to oil droplets entering the combustion chamber from the piston crevice. Residual exhaust gas trapped within the spark plug can also initiate pre-ignition. Knocking, characterized by pressure oscillations, arises from the auto-ignition of hotspots in the end-gas or, potentially, from deflagration-to-detonation transition, although the latter requires further experimental validation. Factors influencing pre-ignition and knocking, including engine oil, in-cylinder deposits, structural hotspots, and the reactivity of the air–fuel mixture, are also analyzed. Based on these factors, the paper concludes that the primary approach to suppressing pre-ignition and knocking in methanol engines is controlling the formation of pre-ignition sources and reducing the reactivity of the air–fuel mixture. Furthermore, it addresses existing issues and limitations in current research, such as combustion testing techniques, numerical simulation accuracy, and the mechanisms of methanol–oil interaction, and offers related recommendations.